Severe hypoglycemia in users of sulfonylurea antidiabetic agents and antihyperlipidemics. Issue 5 (17th January 2016) - Leonard, CE; Bilker, WB; Brensinger, CM; Han, X; Flory, JH; Flockhart, DA; Gagne, JJ; Cardillo, S; Hennessy, S
Abstract : Drug–drug interactions causing severe hypoglycemia due to antidiabetic drugs is a major clinical and public health problem. We assessed whether sulfonylurea use with a statin or fibrate was associated with severe hypoglycemia. We conducted cohort studies of users of glyburide, glipizide, and glimepiride plus a statin or fibrate within a Medicaid population. The outcome was a validated, diagnosis‐based algorithm for severe hypoglycemia. Among 592, 872 persons newly exposed to a sulfonylurea+antihyperlipidemic, the incidence of severe hypoglycemia was 5.8/100 person‐years. Adjusted hazard ratios (HRs) for sulfonylurea+statins were consistent with no association. Most overall HRs for sulfonylurea+fibrate were elevated, with sulfonylurea‐specific adjusted HRs as large as 1.50 (95% confidence interval (CI): 1.24–1.81) for glyburide+gemfibrozil, 1.37 (95% CI: 1.11–1.69) for glipizide+gemfibrozil, and 1.63 (95% CI: 1.29–2.06) for glimepiride+fenofibrate. Concomitant therapy with a sulfonylurea and fibrate is associated with an often delayed increased rate of severe hypoglycemia.